2016
DOI: 10.1002/jat.3397
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics and toxicodynamics of chlorpyrifos is altered in embryos of Japanese medaka exposed to oil sands process‐affected water: evidence for inhibition of P‐glycoprotein

Abstract: Oil sands process-affected water (OSPW) is generated during extraction of bitumen in the surface mining oil sands industry in Alberta, Canada. Studies were performed in vitro by use of Caco-2 cells, and in vivo with larvae of Japanese medaka (Oryzias latipes) to determine if organic compounds from the aqueous phase of OSPW inhibit ATP binding cassette protein ABCB1 (permeability-glycoprotein, P-gp). Neutral and basic fractions of OSPW inhibited activity of P-gp in Caco-2 cells by 1.9- and 2.0-fold, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Naphthenic sulfoxides are water-soluble , but, importantly, nonionized at OSPW pH; ionization is known to limit the bioaccumulation and toxicity of NAs. ,,, Indeed, OS + NAFCs reportedly have among the highest partition coefficients ( K ow ) of all OSPW organics, ,, and are readily solvent extracted at the alkaline pH of OSPW; ,, by contrast, many NAs poorly partition as naphthenate ions. ,, Nonionic petroleum substances (e.g., hydrocarbons, PAHs, alkylphenols) are known to be up to orders of magnitude more potently toxic than NAs; ,,,, thus, it may not be unreasonable to expect naphthenic sulfoxides to be significant toxicants. Although the above results could be partially described through baseline hydrocarbon toxicity, other possible MoAs were not ruled out: e.g., NAFCs have been shown to be uncouplers of oxidative phosphorylation, an MoA with fish EC 50 s (∼0.1–1 mmol/kg) comparable to those inferred for OS + NAFCs herein; sulfoxide NAFCs may also act to magnify the effects of other toxicants through chemosensitization. ,, …”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Naphthenic sulfoxides are water-soluble , but, importantly, nonionized at OSPW pH; ionization is known to limit the bioaccumulation and toxicity of NAs. ,,, Indeed, OS + NAFCs reportedly have among the highest partition coefficients ( K ow ) of all OSPW organics, ,, and are readily solvent extracted at the alkaline pH of OSPW; ,, by contrast, many NAs poorly partition as naphthenate ions. ,, Nonionic petroleum substances (e.g., hydrocarbons, PAHs, alkylphenols) are known to be up to orders of magnitude more potently toxic than NAs; ,,,, thus, it may not be unreasonable to expect naphthenic sulfoxides to be significant toxicants. Although the above results could be partially described through baseline hydrocarbon toxicity, other possible MoAs were not ruled out: e.g., NAFCs have been shown to be uncouplers of oxidative phosphorylation, an MoA with fish EC 50 s (∼0.1–1 mmol/kg) comparable to those inferred for OS + NAFCs herein; sulfoxide NAFCs may also act to magnify the effects of other toxicants through chemosensitization. ,, …”
Section: Resultsmentioning
confidence: 75%
“…Although the above results could be partially described through baseline hydrocarbon toxicity, other possible MoAs were not ruled out: e.g., NAFCs have been shown to be uncouplers of oxidative phosphorylation, 146 an MoA with fish EC 50 s (∼0.1−1 mmol/kg 88 ) comparable to those inferred for OS + NAFCs herein; sulfoxide NAFCs may also act to magnify the effects of other toxicants through chemosensitization. 110,147,148 2) and as predicted by the dose−response models (of Figure 3). Insets: pie (donut) plots of all AEO MS measured in the initial raw OSPWs (t 0 , measurably toxic) and at the first treated sample (t 1 , no measured toxicity), colored according to the PBM-predicted LC 50 (mmol/L) of each NAFC detected�the model predicted that toxic NAFCs constituted a minority of the AEO MS and that their relative abundance declined due to treatment.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The exact mechanism behind the CPM-induced energy stress is not known, but it is interesting to speculate that part of the increased demand for ATP is linked to activation of the P-glycoprotein pump (cellular efflux transporter ABCB1 in mammals, ABCB4 in fish) in order to transport chemical conjugates across cell membranes. The ATP-dependent efflux pump P-glycoprotein has been implicated in the stress response to CPF (Bain and LeBlanc, 1996) and helps protect cells from the effects of a variety of xenobiotics (Fischer et al, 2013; Alharbi et al, 2017). Energy stress might also be linked to perturbations of hepatic fat metabolism, as CPF in mice has been shown to block 21 different metabolic serine hydrolases after in vivo exposure (Medina-Cleghorn et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Gilbert et al [55] showed that heterotrophic grazers such as ciliates may act as biological dispersants of hydrocarbons, contributing to the bioremediation of hydrocarbon contamination by dispersing the lipid droplets that can cut off oxygen to the water column and also prove lethal to macrofauna and flora. Tailings waste has also been applied in vitro to multicellular organisms, including HeLa cells and fish embryos [56,57,58]. These experiments have shown profound local toxicity to these multicellular tissues and organisms, which implies that macrofauna such as fish and plants would struggle to survive in the environmentally challenging conditions of tailings, fresh process water, and early-stage reclamation environments, though the toxicity of end-pit lake waters would certainly decrease over time due to dilution and reclamation processes.…”
Section: In Vitro and In Situ Assessments Of Protists In Reclamatimentioning
confidence: 99%